Psb29, a Conserved 22-kD Protein, Functions in the Biogenesis of Photosystem II Complexes in Synechocystis and Arabidopsis - Keren, Nir (American Society of Plant Biologists, 2005)
Photosystem II (PSII), the enzyme responsible for photosynthetic oxygen evolution, is a rapidly turned over membrane protein complex. However, the factors that regulate biogenesis of PSII are poorly defined. Previous proteomic analysis of the PSII preparations from the cyanobacterium Synechocystis sp PCC 6803 detected a novel protein, Psb29 (Sll1414), homologs of which are found in all cyanobacteria and vascular plants with sequenced genomes. Deletion of psb29 in Synechocystis 6803 results in slower growth rates under high light intensities, increased light sensitivity, and lower PSII efficiency, without affecting the PSII core electron transfer activities. A T-DNA insertion line in the PSB29 gene in Arabidopsis thaliana displays a phenotype similar to that of the Synechocystis mutant. This plant mutant grows slowly and exhibits variegated leaves, and its PSII activity is light sensitive. Low temperature fluorescence emission spectroscopy of both cyanobacterial and plant mutants shows an increase in the proportion of uncoupled proximal antennae in PSII as a function of increasing growth light intensities. The similar phenotypes observed in both plant and cyanobacterial mutants demonstrate that the function of Psb29 has been conserved throughout the evolution of oxygenic photosynthetic organisms and suggest a role for the Psb29 protein in the biogenesis of PSII.